2008
DOI: 10.1093/nar/gkn032
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor- -regulated miR-24 promotes skeletal muscle differentiation

Abstract: MicroRNAs (miRNAs) have recently been proposed as a versatile class of molecules involved in regulation of a variety of biological processes. However, the role of miRNAs in TGF-β-regulated biological processes is poorly addressed. In this study, we found that miR-24 was upregulated during myoblast differentiation and could be inhibited by TGF-β1. Using both a reporter assay and Northern blot analysis, we showed that TGF-β1 repressed miR-24 transcription which was dependent on the presence of Smad3 and a Smads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(215 citation statements)
references
References 55 publications
6
207
0
2
Order By: Relevance
“…Wang et al 43 showed that miR-24 could decrease human ACVR1B expression at mRNA and protein levels. Published evidence 46 showed that this miR-24 is involved in the inhibition of skeletal muscle differentiation by TGFb. Even though miR-24 is not a muscle-specific miRNA, they suggested that miR-24 might function during differentiation and homeostatic maintenance of cardiac and skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 43 showed that miR-24 could decrease human ACVR1B expression at mRNA and protein levels. Published evidence 46 showed that this miR-24 is involved in the inhibition of skeletal muscle differentiation by TGFb. Even though miR-24 is not a muscle-specific miRNA, they suggested that miR-24 might function during differentiation and homeostatic maintenance of cardiac and skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For immunostaining [45], cells were fixed with 4% PFA or 10% TCA, permeabilized with 0.2% Triton X-100/PBS for 5 min followed by blocking with 5% BSA for 1 h, and were incubated with primary antibodies in a humidified box overnight, followed by three 10-min washes with PBS. Secondary antibodies were applied for 1 h followed by three 10-min washes with PBS, and cells were counter-stained with DAPI and mounted with Prolong Gold antifade reagent (Invitrogen).…”
Section: Immunostaining and Immunoblottingmentioning
confidence: 99%
“…TGF-b expression during RSV infection has been shown to be important for cell cycle inhibition in the G 0 /G 1 phase (Gibbs et al, 2009;McCann & Imani, 2007;Wu et al, 2011) and miR-24 has been shown to be suppressed by TGF-b (Sun et al, 2008), as well as regulate TGF-b precursor processing (Luna et al, 2011). As preliminary data showed a role for NS1 in regulating miR-24 expression, the impact of NS1 overexpression on TGF-b expression was determined.…”
Section: Rsv Ns1 Modulates Tgf-b Expression Via Klf6mentioning
confidence: 99%
“…TGF-b treatment has been shown to increase RSV replication in A549 as well as primary NHBE cells (Gibbs et al, 2009). TGF-b has also been shown to inhibit miR-24 expression in other cell types (Cao et al, 2012;Sun et al, 2008) …”
Section: Silencing Klf6 Induces Mir-24 and Tgf-b Treatment Represses mentioning
confidence: 99%